Religious extremism and radicalisation of Muslims in Malaysia: the Malay ties with the Mujahidin, al Qaeda and ISIS - Jaafar, Muhammad Izzuddin; Akhmetova, Elmira (Universiti Sultan Zainal Abidin, 2020)
This study discusses the reasons behind the rise of religious extremism in Malaysia within the framework of international politics and the world order by highlighting the ties of Malay Muslims with the Mujahidin, Al Qaeda and the Islamic State of Iraq and Syria (ISIS) over the last four decades. For that purpose, a qualitative analytical approach is used, Referencing secondary sources such as academic journal articles and scholarly books. In understanding the situation, online newspaper articles were also considered as secondary sources to extract the data to understand the destructive situation in Malaysia, which has gradually become a fertile ground for the sowing of radical ideas. The paper highlights that since the 1970s, religious extremism and radicalism have intensified due to the Cold War politics, the conflict between Palestine and Israel, and, later, foreign invasions of Muslim nation-states, giving rise to many local religious extremist groups with their relations to international extremist groups. Analysis of the secondary sources reveals the existence of a radical understanding of Islam by a substantial portion of the population, thus suggesting that the authorities should pay attention to extremist influences on the moderate nature of social relations in multi-ethnic and multi-religious Malaysia. At the same time, the paper argues that this negative transformation cannot be explained by external factors alone, as the internal factors have played an important role in the radicalisation of Malay society. The paper concludes with several practical recommendations such as improvisation of religious education that emphasises on peaceful cohesion, and discontinuation of foreign intervention policies and over generalisations. These recommendations are to regulate the escalation of extremism and radical understanding of Islam in Malaysia, which considerably threatens national security and citizens’ wellbeing.